2019
DOI: 10.1002/jcb.29512
|View full text |Cite
|
Sign up to set email alerts
|

In vitro knock‐out of miR‐155 suppresses leukemic and HCV virus loads in pediatric HCV‐4–associated acute lymphoid leukemia: A promising target therapy

Abstract: Hepatitis C virus (HCV) infection is a major public health problem, having a high prevalence in Egypt. Leukemia and lymphoma have been associated with HCV infection. MicroRNA‐155 (miR‐155) has been reported to play a regulatory role in cancer, inflammation, and immune response to infection. The expression level of miR‐155 in HCV viremic patients is controversial; although high miR‐155 levels were demonstrated in HCV genotypes 1,2, and 3, low levels of miR‐155 were detected in Egyptian patients with HCV genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
(68 reference statements)
1
8
0
Order By: Relevance
“…For example, miR-155 and miR-139-5p can constitute a negative feedback loop in the NF-κB signaling pathway by targeting multiple key proteins, leading to the repression of NF-κB activation in response to viral or microbial stimuli 19,20 . The expression of miR-155 was enhanced in microglial cells during Japanese encephalitis virus (JEV) infection, and JEV-induced IFN-β as well as downstream ISG mRNA expression was significantly reduced in microglial overexpressing miR-155 19 .The knock-out or inhibition of miR-155 decreases hepatitis C virus (HCV) viremia in children with leukemia 22 . miR-29b is capable of inhibiting the JAK-STAT signaling pathway by IFN-γ in CD8 + T cells and TH1 effector cells 21 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-155 and miR-139-5p can constitute a negative feedback loop in the NF-κB signaling pathway by targeting multiple key proteins, leading to the repression of NF-κB activation in response to viral or microbial stimuli 19,20 . The expression of miR-155 was enhanced in microglial cells during Japanese encephalitis virus (JEV) infection, and JEV-induced IFN-β as well as downstream ISG mRNA expression was significantly reduced in microglial overexpressing miR-155 19 .The knock-out or inhibition of miR-155 decreases hepatitis C virus (HCV) viremia in children with leukemia 22 . miR-29b is capable of inhibiting the JAK-STAT signaling pathway by IFN-γ in CD8 + T cells and TH1 effector cells 21 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Fognani and co-workers described a significant increase in the expression of three oncomiRs, miR-21, miR-155, and miR-16 in PBMCs from the HCV-NHL subgroup. MiR-21 and miR-155 were previously associated with pro-survival activity and autoimmunity disorders [83,84] and recent evidence has suggested that miR-155 could be a therapeutic target in patients with both HCV-chronic infection and leukemia [85]. In fact, the authors performed an in vitro knockout of miR-155 in primary lymphoid cultures from pediatric patients and observed an inhibition on leukemic cell proliferation and viral replication [85].…”
Section: Micrornas In Hcv-related Lymphomas and Lymphoproliferative Dmentioning
confidence: 99%
“…MiR-21 and miR-155 were previously associated with pro-survival activity and autoimmunity disorders [83,84] and recent evidence has suggested that miR-155 could be a therapeutic target in patients with both HCV-chronic infection and leukemia [85]. In fact, the authors performed an in vitro knockout of miR-155 in primary lymphoid cultures from pediatric patients and observed an inhibition on leukemic cell proliferation and viral replication [85]. MiR-155 expression is controlled by a wide range of signaling pathways, but its role as oncomiR is well defined in immune response and inflammation [86].…”
Section: Micrornas In Hcv-related Lymphomas and Lymphoproliferative Dmentioning
confidence: 99%
“…An important role of miR-155, besides inflammation and immune response to infection, is the regulatory role in cancer [107]. It can influence the hematopoiesis, acting as an oncomiR in different types of leukemia or lymphoma but also in solid tumors.…”
Section: Cellular Physiologymentioning
confidence: 99%
“…Overexpression of miR-155 is reported in CLL [87,108], AML [89,109], DLBLC where it is considered an independent prognosis indicator of survival [110][111][112][113][114][115][116], Hodgkin lymphoma [88], or NK cell lymphomas [117]. Hassan et al have proven the miR-155 implications in pediatric patients with AML associated with hepatitis C virus (HCV) infection and found that this miRNA is linked to high HCV viral load and leukemic burden and demonstrated that miR-155a knockout can improve the disease outcome [107].…”
Section: Cellular Physiologymentioning
confidence: 99%